Female and Male Infertility Causes and Homoeopathic Management (Homoeopathy for All, 2024)
Infertility is considered a condition  in which a woman is unable to  become pregnant despite having  regular intercourse for more than  12 months without the use of birth  control pills and condoms. The  incidence of infertility is increasing  worldwide due to many factors such  as ovulatory problem, oligospermia,  diabetes, pituitary factors nutrition,  lifestyle, hormonal health factors  and environmental factors. Infertility  has psychological and social  impact. According to research,  approximately one in six couples  are infertile. Here homeopathic  medicines help in pregnancy by  eliminating or by curing the disease,  there are many things we can control  but when all the tests are normal and  no causes are found homeopathic  medicine plays an important role in  this because sometimes homeopathic  medicine works on the symptoms  which are obstacles in pregnancy. It  may be occurring due to per vaginal  discharge, irregular menstrual  bleeding, erectile dysfunction  homeopathy plays an important role  to manage this condition.
Keywords: Infertility; Pregnancy; leucorrhoea; sterility